Poznawanie prawdy i zdolność przewidywania w naukach przyrodniczych - Irena Grochowska (Studia Ecologiae et Bioethicae)
Representatives of natural sciences (biologists, physicists, chemists) are scientists who deal with the part of knowledge regarding aspects of natural reality. If we regard natural reality to cosmos we can say that the possibilities of direct research are possible only in a small area. In spite of the limitations of access researchers do not get lost in the chaos of already studied separate images, but the gained experience, together with evolution of human thought create more and more uniform image, despite of numerous missing pieces.